Low-frequency weak electric field measurement based on Rydberg atoms using cavity-enhanced three photon system - Xiao, Dongping; Shi, Zhuxin; Chen, Lin; Yan, Sheng; Xu, Lanxin; Zhang, Huaiqing (Frontiers in Physics, 2024)
Rydberg atoms are ideal for measuring electric fields due to their unique physical properties. However, low-frequency electric fields below MHz can be challenging due to the accumulation of ionized free electrons on the atomic vapor cell's surface, acting as a shield. This paper proposes a Cavity-enhanced three-photon system (CETPS) measurement scheme, which uses a long-wavelength laser to excite the Rydberg state, reducing atomic ionization and enhancing detection spectrum resolution. A theoretical model is proposed to explain the quantum coherence effect of the light field, measured electric field, and the atomic system. The results show that the proposed scheme significantly increases the EIT spectral peak and narrows the spectral width, resulting in the maximum slope increasing by more than an order of magnitude. The paper also discusses the impact of the Rabi frequency of the two laser fields and the coupling coefficient of the optical cavity on the transmission spectrum amplitude and linewidth, along with the optimal configuration of these parameters in the CEPTS scheme.